2008
DOI: 10.1017/s0950268808001179
|View full text |Cite
|
Sign up to set email alerts
|

A survey of laboratory-confirmed isolates of invasive listeriosis in Israel, 1997–2007

Abstract: During the 11-year period from 1997 to 2007, 321 isolates of Listeria monocytogenes from sporadic cases of invasive listeriosis were reported to the national reference laboratory in Israel. Of these isolates, 113 (35%) were identified from perinatal cases, and 208 (65%) from non-perinatal cases. The prevalent serovars were 4b, 1/2b, 1/2a and 4c. Serovar 4b was identified in 80.5% of the perinatal isolates (P=0.0162), while the number of 1/2b and 1/2a strains increased in the > or = 60 years old group (P=0.0285… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
(36 reference statements)
0
8
0
3
Order By: Relevance
“…This causes the selective pressure that encourages the development of resistance in these pathogens especially via gene alterations or acquisition of mobile genetic elements [23]. In 1988, multidrug-resistant (MDR) L. monocytogenes was first isolated from a patient in France that suffered from meningoencephalitis [24]. In 1990, the first acquired antibiotic resistance in L. monocytogenes was described [25].…”
mentioning
confidence: 99%
“…This causes the selective pressure that encourages the development of resistance in these pathogens especially via gene alterations or acquisition of mobile genetic elements [23]. In 1988, multidrug-resistant (MDR) L. monocytogenes was first isolated from a patient in France that suffered from meningoencephalitis [24]. In 1990, the first acquired antibiotic resistance in L. monocytogenes was described [25].…”
mentioning
confidence: 99%
“…One study from Taiwan reported that more than 36.7% of patients acquired invasive listeriosis in the spring [15], While research from England and Wales reported that summer was the predominant season of listeriosis onset [18]. In Israel, the incidence in nonperinatal women was 64.2% in the hot season (May-october) [19]. A study from France documented an increase of cases during the summer [20].…”
Section: Discussionmentioning
confidence: 99%
“…Este hecho contrasta con la distribución estacional conocida para los países del hemisferio norte donde la mayor concentración de casos se da en estos meses [22][23][24] , aunque en Finlandia se da un patrón mixto con casos en invierno y verano 25 . En el Reino Unido, el aumento estacional de casos ha sido asociado mediante modelos matemáticos a la temperatura del mes en curso o del mes precedente 24 , una explicación no aplicable a nuestro país por la baja incidencia de casos en verano.…”
Section: Epidemiología Y Prevenciónunclassified